Self-Esteem, Study Habits and Academic Performance among University Students - Kasyoka, Antony (African Journal of Education and Practice, 2023)
Purpose: This study intended to investigate the relationship between self-esteem and study habits on the academic performance of students in universities. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings of the study revealed the existence of a contextual and methodological gap relating to self- esteem and study habits on the academic performance of university students. Preliminary empirical review found that self-esteem does not account for low or high academic performance, as most students reported enjoying a good level of self-esteem, regardless of their grades. However, the same is not true of study habits, which are tied to academic performance as shown by our results and prior research. Hence better performance is expected of students if their study techniques are to improve. Unique Contribution to Theory, Practice and Policy: The Social Learning and Cognitive Evaluation theories may be used to anchor future studies on self-esteem and study habits on the academic performance of university students. In terms of self-esteem, improvement thereof is not an urgent matter as nearly all students claim a good level of self-esteem, hence it would be appropriate to consider other variables for future research.